Soil chemical properties in vineyard areas in the southern region of the state of Santa Catarina, Brazil - Bordallo, Samya Uchôa; Bueno, Alcenir Claudio; Ferreira, Guilherme Wilbert; Bruna, Emilio Dela; Serpa, Izabela Sgrott; Brunetto, Gustavo; Comin, Jucinei José; Lovato, Paulo Emílio; Lourenzi, Cledimar Rogério (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate changes in the soil chemical properties and the critical environmental limit for phosphorus (CEL-P) in vineyards, in the southern region of the state of Santa Catarina, Brazil. Soil samples were collected at 0–5, 5–10, 10–20, and 20–40 cm soil depths, in vineyards aged 22, 36, and 60 years, and in the area of an adjacent native forest. The following parameters were analyzed: granulometry, pH in water, and exchangeable Al levels, to obtain potential acidity and Al saturation; and available levels of P and K, and exchangeable levels of Ca and Mg, to determine base saturation, cation exchange capacity; and soil organic matter (SOM). In comparison with the forest soil, the vineyard soils showed increased pH values, P, K, Ca, Mg, Cu, Zn, and SOM levels, and base saturation, as well reduced Al saturation, with more accentuated effects in areas with the longest cultivation time. The vineyards show changes in soil chemical properties with time and P levels above the CEL-P, at least in one of the soil layers.